Kepemimpinan Spiritual Kepala Sekolah Dalam Meningkatkan Budaya Religius Siswa di SMA Sunan Kalijogo Jabung Malang - At-Turmudzi, Aufa Husna Aulia; Anwar, Khoirul (Impressive: Journal of Education, 2025)
Leadership and spirituality are closely related, recalling that humans are caliphs on earth, however, how high the level of spirituality is is not the same. Researchers are interested in studying because in their journey leadership has a spirit in the name of God. The interrelationship of students' religious culture in schools. So connected with the spiritual leadership of the school principal in instilling religious culture in students, so the research title was born "School Principal's Spiritual Leadership in Improving Students' Religious Culture at SMA Sunan Kalijogo Jabung Malang".The purpose of this research is to find out the spiritual leadership of the principal at SMA Sunan Kalijogo Jabung, and secondly, to find out how to improve religious culture at SMA Sunan Kalijogo Jabung. This research uses a descriptive approach method, with a type of qualitative research. Qualitative research tends to be phenomorphic. The research informants were school principals, student vice presidents, curriculum assistant teachers, and students. While the secondary data source in this study is documentation related to this research. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results showed (1) the spiritual leadership of the principal in improving the religious culture of students at SMA Sunan Kalijogo Jabung Malang has been carried out according to the characteristics of vision, altrustic love, and hope/faith which are strong foundations in creating a religious culture. (2) Improving the religious culture of students, by the school principal by creating and instilling Islamic values through religious programs in schools so that the soul and character of the Islamic religion can be formed in the school environment.